Analisis Kemampuan Matematis Mahasiswa pada Materi Deret Aritmetika dalam Kontekstualisasi Masalah Ekonomi - Morin, Shelly (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2026)
This study aims to analyze students' mathematical application skills in using arithmetic and geometric series concepts in the context of economic decision making. These skills are important because the application of series concepts in business and economics, such as in investment analysis, compound interest, and asset growth and depreciation calculations, requires mathematical understanding that is not only conceptual but also applicable. This study uses a qualitative descriptive approach with subjects being students of the Mathematics Education study program who have taken the Economics and Business Mathematics course. Data were collected through contextual problem-solving tests and semi-structured interviews to explore students' application abilities and reasoningThe results show that most students are able to identify patterns and apply arithmetic and geometric series formulas well, but still have difficulty relating the calculation results to real economic contexts. It was also found that students with high mathematical modeling abilities tend to make more rational and argumentative economic decisions. This study recommends the need to strengthen context-based learning and economic modeling in economic mathematics lectures in order to improve students' mathematical application skills.